Transfusion practice in neonates - Do-Hyun Kim (Korean Pediatric Society, 2018)
Neonates, especially extremely low birth weight infants, are among the groups of patients undergoing transfusion frequently. Since they are exposed to higher specific transfusion risks compared to the patients of other age groups, there are many special aspects that must be considered for transfusion therapy in neonates. The transfusion risks in neonates include adverse outcomes specific for preterm infants as well as increased metabolic, immunologic, and infectious complications. To reduce the risks of transfusion-transmitted cytomegalovirus infection and transfusion-associated graft-versus-host disease, leukoreduced and irradiated cellular blood products should be used for all neonates. This review summarizes the risks of neonatal transfusion therapy, specific methods to reduce risk, and current trends and practices of red blood cell and platelet transfusions in neonates, to facilitate decision-making for neonatal transfusion.